1985
DOI: 10.1016/0021-9797(85)90030-x
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation in a shear field generated by stirring in a cylindrical vessel

Abstract: The coagulation of aqueous ZnO dispersions is investigated at various shear rates, in a shear field generated by stirring in a cylindrical vessel, and at different ~" potential values. Laser Doppler anemometry measurements permitted the construction of a model of the shear field by which average shear rates could be calculated. At low shear rates (~<200 sec-~), the experimental capture efficiencies are independent of the ~" potential (-20 ~" > -3 2 mV). At larger shear rates, the capture efficiencies rise with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…A third method treated each volume element as a separate batch reactor and a volume average of the population size class balance was subsequently obtained. The modeling of independent volume elements was considered due to the hypotheses of several prior researchers (28)(29)(30). These previous researchers suggested that dividing the flow domain into regions of nearly equal flow parameters (strain rate, velocity gradient, or energy dissipation) would yield improved coagulation modeling results.…”
Section: Modeling Analysis Resultsmentioning
confidence: 99%
“…A third method treated each volume element as a separate batch reactor and a volume average of the population size class balance was subsequently obtained. The modeling of independent volume elements was considered due to the hypotheses of several prior researchers (28)(29)(30). These previous researchers suggested that dividing the flow domain into regions of nearly equal flow parameters (strain rate, velocity gradient, or energy dissipation) would yield improved coagulation modeling results.…”
Section: Modeling Analysis Resultsmentioning
confidence: 99%
“…Electrokinetic and coagulation rate measurements were performed in dilute suspensions (3.2 mg in 25 ml), prepared as described previously (10). Adjustment of the pH in the initial suspension was much more rapid for preheated ZnO than for ZnO a.r.…”
Section: Methodsmentioning
confidence: 99%
“…Coagulation rates were determined in a stirred cylindrical vessel using a stirring speed of 700 rpm [9,14].…”
Section: Determinationmentioning
confidence: 99%